Neuropathology of SUDEP: Role of inflammation, blood-brain barrier impairment, and hypoxia. (7th February 2017) - Michalak, Zuzanna; Obari, Dima; Ellis, Matthew; Thom, Maria; Sisodiya, Sanjay M.
Abstract : Objective: To seek a neuropathologic signature of sudden unexpected death in epilepsy (SUDEP) in a postmortem cohort by use of immunohistochemistry for specific markers of inflammation, gliosis, acute neuronal injury due to hypoxia, and blood-brain barrier (BBB) disruption, enabling the generation of hypotheses about potential mechanisms of death in SUDEP. Methods: Using immunohistochemistry, we investigated the expression of 6 markers (CD163, human leukocyte antigen–antigen D related, glial fibrillary acid protein, hypoxia-inducible factor-1α [HIF-1α], immunoglobulin G, and albumin) in the hippocampus, amygdala, and medulla in 58 postmortem cases: 28 SUDEP (definite and probable), 12 epilepsy controls, and 18 nonepileptic sudden death controls. A semiquantitative measure of immunoreactivity was scored for all markers used, and quantitative image analysis was carried out for selected markers. Results: Immunoreactivity was observed for all markers used within all studied brain regions and groups. Immunoreactivity for inflammatory reaction, BBB leakage, and HIF-1α in SUDEP cases was not different from that seen in control groups. Conclusions: This study represents a starting point to explore by immunohistochemistry the mechanisms underlying SUDEP in human brain tissue. Our approach highlights the potential and importance of considering immunohistochemical analysis to help identify biomarkers of SUDEP. Our results suggest that with the markers used, there is no clear immunohistochemical signature of SUDEP in human brain.